The clinical potential and limits of the all-ceramic fixed partial denture restorations - Harry Laksono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
High-strength all-ceramic systems for fixed partial dentures (FPDs) is gaining popularity as an alternative to the well established metal-ceramic FPDs. Several new framework materials and technique such as lithium disilicate, aluminum oxide and yttrium tetragonal zirconia polycrystal have been developed with improved strength, marginal discrepancy and esthetics. Since not every all-ceramic system can be used for a variety application, proper selection of the materials is an important for the success of all-ceramic FPDs. The longevity of dental restorations is an important health concern and the clinician placed great emphasis on mechanical properties to define the clinical indication of the ceramic materials because of their brittleness and low fracture toughness. The stronger and tougher framework material would improve the reliability and the longevity of dental restoration. To fabricated of an all-ceramic FPDs, material would be required with a flexural strength in excess of 300 MPa and fracture toughness 3 MPa/m½. Zirconium has a better mechanical properties than alumina and lithium disilicate glass-ceramic, result from the transformation toughening, free of glass phase and minimal flaws. Whereas lithium disilicate glass-ceramic has a better translucency than alumina and zirconium based ceramic, result from the higher content of glass phase than that two materials. The purpose of this article is to present the information that can guide the practioner in the decision making process about all-ceramic FPDs systems. It can be concluded that the all-ceramic FPDs are seems to be an acceptable clinically prosthodontic treatment according to the short-term studies and the lithium disilicate and alumina-based ceramic materials are acceptable for 3 units anterior FPDs, whereas zirconia-based ceramic are acceptable for 3–5 units anterior and posterior FPDs with 2 pontics. However, further investigation and more clinical long-term follow-up studies are needed.